Implementasi Asistensi Pelaporan SPT Tahunan Wajib Pajak Orang Pribadi oleh Relawan Pajak - Handayani, Yupita Riskia; Biswas, Nurani Putri; Akbar, Hikmal; Isnaini, Zuhrotul (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to analyze the implementation of the annual tax return (SPT) assistance program by tax volunteers at KPP Pratama Mataram Timur and its contribution to the literacy and compliance of individual taxpayers. This research employs a descriptive qualitative method, collecting data through observations, in-depth interviews, and documentation. The findings reveal that tax volunteers facilitated the SPT reporting process, particularly for first-time e-Filling users. The hands-on approach, conducted without visual educational aids, proved effective in enhancing taxpayer understanding. However, the program faced technical challenges such as unstable internet connections and limited service space. The implications highlight the need for strengthening infrastructure support, continuous volunteer training, and formal collaboration between DJP, KPP, and educational institutions to ensure the effectiveness and sustainability of the assistance program.